Electro-magnetic Sensors for Online Condition Monitoring of Medium Voltage Cables - Shafiq, Muhammad; Kauhaniemi, Kimmo; Hussain, Amjad; Kutt, Lauri (AMA Association for Sensors & Measurement, 2020)
Increased use of medium voltage (MV) cables demands for efficient condition monitoring in order to carry out timely predictive maintenance especially during incipient fault conditions emerging due to insulation degradation. This paper presents a comparison of the design and performance parameters of the Rogowski coil and high frequency current transformer sensors for measurement of partial discharge (PD) signals emitted from the PD defects. This work is performed in the laboratory environment that provides a practical approach for developing electromagnetic sensor for PD measurements.
Keywords: Distribution Network; Electromagnetic sensor; Medium voltage cable; partial discharge; condition monitoring; fi=Sähkötekniikka|en=Electrical Engineering|